2020
DOI: 10.1108/md-01-2019-0110
|View full text |Cite
|
Sign up to set email alerts
|

A strategic decision making tool for new product and service design

Abstract: PurposeThe present study aims to further research the theory of attractive quality for new offers by analyzing the HWWP (Health, Weapon, Wealth, Prospect) model and testing its uniformity. The purpose is to extend and refine the HWWP model based on meridian elasticity curves with the final scope of building a map for better understanding the potential value of the quality attributes in new product or strategic service design.Design/methodology/approachAfter a thorough analysis of the HWWP model for prepurchase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In addition, [43] observed that managers can foster an organization's environmental values and beliefs and include a vision of corporate sustainability that is ingrained into a business vision and mission that creates a common corporate identity. Ref [44] pointed out that the promotion and support Ref [45] posited that environmental values and goals must be embedded in and pursued by all corporate departments to achieve corporate sustainability. An organizational culture focused on sustainability can be a competitive advantage, for example in developing innovative ways of reducing costs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, [43] observed that managers can foster an organization's environmental values and beliefs and include a vision of corporate sustainability that is ingrained into a business vision and mission that creates a common corporate identity. Ref [44] pointed out that the promotion and support Ref [45] posited that environmental values and goals must be embedded in and pursued by all corporate departments to achieve corporate sustainability. An organizational culture focused on sustainability can be a competitive advantage, for example in developing innovative ways of reducing costs.…”
Section: Resultsmentioning
confidence: 99%
“…QDT needs more rigorous empirical research into "its real-life value" (Pothos & Busemeyer, 2013;Antoni et al, 2019). The very gap between QDT's theoretical elegance and its empirical challenges raises an important question for future studies (Pugna et al, 2020). QDT offers a new perspective on strategic decision-making, but it is still an evolving area that comes with difficulties of its own.…”
Section: Implications For Strategymentioning
confidence: 99%
“…However, Kano’s model is known as the three-factor theory of customer satisfaction by some researchers (Matzler and Sauerwein, 2002; Yuan et al , 2018). In addition to management and tourism, this approach is used in areas such as industrial engineering as a tool to improve services (Borgianni, 2018; Haktanır and Kahraman, 2019; He et al , 2017; Pugna et al , 2021; Roy and Mukherjee, 2017).…”
Section: Theoretical Foundationsmentioning
confidence: 99%